That's the one! - Ashley, Bernard; Trasher, Janee (Laguna Hills, CA : QEB Pub., 2007)
When Billy accompanies his mum to buy a new dress for her and a birthday present for himself, they both have a hard time deciding on just the right thing.
Keywords: Shopping -- Fiction; Clothing and dress -- Fiction; Imagination -- Fiction